PENERAPAN MODEL UTAUT UNTUK PERILAKU PENGGUNA “PAYLATER” DI DALAM TRAVELOKA - Amirul Mukminin; Rizal Rachman; Hery Wahyudi (Jurnal Computech & Bisnis (e-Journal), 2019)
The development of E-commerce makes "PayLater" at Traveloka become popular among Indonesians. "PayLater" at Traveloka has proven to have great benefits for the community because it provides convenience in the affairs of use at Traveloka it self . The purpose of this study is to find out and explain the influence of performance expectations, effort expectations, social influences, and facilitating conditions on behavioral intentions using the UTAUT model with a test descriptive, validity, reliability, classical assumptions and multiple linear regression. The population in this study were "PayLater" users at Traveloka who were in the Bandung City area, and determined 100 members as the study sample. From the results of multiple linear regression analysis it can be concluded that the variable performance expectancy has a significant positive effect on behavioral intention, the effort expectancy variable has a positive significant effect on behavioral intention, social influence has a positive significant effect on behavioral intention, and facilitating conditions have a positive significant effect on behavioral intention with an influence (coefficient of determination) of 51.1% and correlation value (R) that is equal to 0.639 which is categorized as very strong. Keyword : UTAUT, PayLater, Performance Expectancy, Effort ExpectancyDOI : http://doi.org/10.5281/zenodo.3631049